Débat hygiénique d’un bâtiment d’élevage additionné de grignon d’olive et de pulpe d’orange et la flore intestinale de poulet de chair. - BOUZIANE, Amel (My University, 2021)
This work is interested in studying the effect of diets containing olive pomace and orange pulp on the health of a barn and the intestinal flora of chicken of flesh. A total of 500 asexual, 1-day-old Arbor-Acres chickens were raised on the ground and receiving a standard diet, and a standard diet with the addition of olive pomace and pulp orange Samples were taken from animals, poultry equipment and staff as well as on the litter and the walls every 15th day throughout the breeding period for carry out microbiological analysis on germs responsible for harming public health(FTAM, faecal and total coliforms, staphylococcus aureus and salmonella). digestive flora, the samples were taken from 14 meat chicken intestines which received a diet supplemented with olive pomace and orange pulp, Data collection was concerned the research of lactic acid bacteria and enterobacteria and identification of some strain isolated using the Api20e gallery. The results showed that the level of contamination with total germs, total and fecal coliforms and staphylococcus aureus, is lowest in the groups of chickens for which we administered pomace olive. Using GO and PO diets can minimize the presence of Enterobacteriaceae in the intestine we recorded values of 353, 60colonies respectively compared to to the control (425), On the other hand we found that the chickens fed with a GO diet exhibits a high number of lactic acid bacteria compared to PO and control. According to the identification test by the api20e gallery we recorded the presence of ecoli type 2 and hermanii in chickens fed with orange pulp compared to the group received from olive pomace which has E. Coli vulnerabilities.
Keywords: health conditions, digestive flora, broilers, E coli, lactic acid bacteria.